Dampak Game Online Mobile Legends terhadap Siswa SD di Lingkungan XII Kecamatan Medan Denai Kelurahan Binjai - Nadrah Hafifah Sahid; Anang Anas Azhar; Zuhriah Zuhriah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This article aims to discuss the impact of Mobile Legends on Elementary School students in Lingkungan XII, Medan Denai District, Binjai Village. This research is a type of quantitative research. The objects in this study were elementary school students in Lingkungan XII. The research was conducted on 55 students, including students in grades 5 and 6. The research was conducted using a simple random sampling system in sampling, and sampling using the Slovin formula with an error rate of 10%, a sample of 35 people was determined, and the data obtained was from a questionnaire. The theory used in this study is new media and the uses and effects theory. The results of the study show that online mobile legends games have an impact on elementary school students in Lingkungan XII Medan Denai, Binjai Village. Most of them started to be lazy to learn since they knew and played mobile legends online games.